The American village in a global setting : selected papers from an interdisciplinary conference in honour of Sinclair Lewis and Ida K. Compton /: selected papers from an interdisciplinary conference in honour of Sinclair Lewis and Ida K. Compton. (2007) - Unknown
No abstract available